2021
DOI: 10.36488/cmac.2021.3.293-303
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and antimicrobial therapy modification during COVID19 pandemic in large tertiary hospital

Abstract: Objective. assessment of the evolution of the microbiological landscape of the hospital for the period of operation in 2020 into a pandemic of a new coronavirus infection in various departments, including intensive care units; change depending on the results of antibacterial therapy regimens. Materials and Methods. In a retrospective study, conducted from June to December 2020, in a multidisciplinary hospital working with COVID-19 infection, the resistance of isolated strains of microorganisms was analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…This trend is confirmed by the results of other Russian and international studies. [19][20][21] For instance, in a study by Maes et al, [19] no significant differences in bacterial pathogens were found between patients with ventilator-associated pneumonia with and without COVID-19. However, the COVID-19 group had a significantly higher risk of developing ventilator-associated pneumonia, as well as isolated cases of invasive aspergillosis.…”
Section: Discussionmentioning
confidence: 95%
“…This trend is confirmed by the results of other Russian and international studies. [19][20][21] For instance, in a study by Maes et al, [19] no significant differences in bacterial pathogens were found between patients with ventilator-associated pneumonia with and without COVID-19. However, the COVID-19 group had a significantly higher risk of developing ventilator-associated pneumonia, as well as isolated cases of invasive aspergillosis.…”
Section: Discussionmentioning
confidence: 95%
“…Хотя устойчивость микроорганизмов к АМП на се годняшний день не является новой проблемой, распро странение резистентных микроорганизмов представляет собой одну из ведущих угроз здравоохранению во всем мире [1,2]. Особенно настораживает ситуация с рас пространением устойчивых нозокомиальных штаммов, которые зачастую вызывают тяжелые бактериальные инфекции, заканчивающиеся летальным исходом [14].…”
Section: Discussionunclassified
“…Emergent antibiotic resistance following the global response to COVID-19 has already been described as “the silent pandemic” [ 2 ], which emphasizes the importance of prudent use of AMD in this group of patients. The preliminary data on COVID-19 influence on epidemiology of nosocomial infections and antimicrobial resistance in Russian hospitals were diverse and inconclusive [ 21 ], but a study performed in a hematological center in Kazakhstan showed a prominent increase in the prevalence of resistant nosocomial isolates; the share of Pseudomonas aeruginosa carbapenemase-producing strains increased from 0% in the pre-pandemic period to 30.4%; the share of methicillin-resistant Staphylococcus aureus increased from 11.8% to 35%, respectively [ 22 ]. The selection of resistance to antibiotics combined with the lack of perspectives for the introduction of new drugs in clinical practice in the near future highlights the urgent need to reassess the practice of AMD prescribing.…”
Section: Discussionmentioning
confidence: 99%